2019
DOI: 10.4049/jimmunol.1800650
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitive IFN Responses in Lupus Keratinocytes Reveal Key Mechanistic Determinants in Cutaneous Lupus

Abstract: The sequences presented in this article have been submitted to the Gene Expression Omnibus (https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE124939) under accession number GSE124939.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…Keratinocytes from patients with SLE demonstrate low expression of barrier-related genes and increased adherence to S. aureus Given that IFNs downregulate barrier genes and nonlesional keratinocytes from patients with SLE express elevated type I IFNs (IFN-k) at baseline (Sarkar et al, 2018), we next explored whether barrier genes were differentially expressed in nonlesional SLE and control keratinocytes (HCs). To this end, keratinocytes were obtained from nonlesional skin and subjected to RNA sequencing analysis as reported previously (Tsoi et al, 2019). Barrier genes such as FLG, LOR, IVL, and CLDN1, as well as antimicrobial peptides (DEFB), were repressed in SLE keratinocytes in comparison with HC keratinocytes ( Figure 4).…”
Section: Exposure To Ifns Results In Diminished Barrier Gene Expressionmentioning
confidence: 88%
See 1 more Smart Citation
“…Keratinocytes from patients with SLE demonstrate low expression of barrier-related genes and increased adherence to S. aureus Given that IFNs downregulate barrier genes and nonlesional keratinocytes from patients with SLE express elevated type I IFNs (IFN-k) at baseline (Sarkar et al, 2018), we next explored whether barrier genes were differentially expressed in nonlesional SLE and control keratinocytes (HCs). To this end, keratinocytes were obtained from nonlesional skin and subjected to RNA sequencing analysis as reported previously (Tsoi et al, 2019). Barrier genes such as FLG, LOR, IVL, and CLDN1, as well as antimicrobial peptides (DEFB), were repressed in SLE keratinocytes in comparison with HC keratinocytes ( Figure 4).…”
Section: Exposure To Ifns Results In Diminished Barrier Gene Expressionmentioning
confidence: 88%
“…RNA sequencing data was obtained from keratinocytes isolated from nonlesional control and systemic lupus erythematosus skin as previously reported (RNA sequencing data is available in Gene Expression Omnibus; accession number GSE124939) (Tsoi et al, 2019). RNA sequencing log 2 expression values were averaged for each selected gene in each condition.…”
Section: Rna Sequencing Data Analysis and Gene Expression Heatmapmentioning
confidence: 99%
“…Given these data, we next hypothesized that structural cells in the skin may be key responders to IFN-λ and coordinate immune responses through expression of proinflammatory chemokines. Keratinocytes are the most abundant cell type in the skin and have been implicated in the pathogenesis of SLE and other inflammatory skin diseases (36,37). Previous reports have indicated that keratinocytes express the IFNLR and respond to stimulation with IFN-λ cytokine (11,22,38).…”
Section: Ifn-λ Promotes Skin Inflammation and Induces Chemokine Exprementioning
confidence: 99%
“…Further investigation revealed that Ifnlr1 −/− mice had lower expression of proinflammatory cytokines and chemokines (IL6, CXCL9, CXCL10) in skin tissue. Keratinocytes are the most abundant cell type in skin and have been implicated in SLE and a variety of other inflammatory skin diseases (36,37). Previous reports suggest that keratinocytes respond to IFN-λ in vitro (11,38).…”
Section: Ifn-λ Promotes Lupus-associated Renal Pathology and Activatesmentioning
confidence: 99%
“…Keratinocytes from CLE patients exhibit an enhanced response to both type-1 and type-2 IFNs ( 156 ), and produce IFNκ ( 157 ), IL-6 ( 158 ), and Type-III IFN (IFNλ) following UVB damage. Cytokine dysregulation in UVB treated CLE keratinocytes provides a link between UV initiation factors and immunopathogenesis ( 156 ). UV treatment of keratinocytes induces upregulation of IFNκ, which plays a key homeostatic role in maintaining IFN balance in skin ( 158 ).…”
Section: Cle Immunopathogenesismentioning
confidence: 99%